Clearing of hemozoin crystals in malaria parasites enables whole-cell STED microscopy - Kehrer, Jessica; Pietsch, Emma; Heinze, Julia; Spielmann, Tobias; Frischknecht, Friedrich (Journal of cell science, 2023)
Malaria is a devastating mosquito-borne parasitic disease that manifests when Plasmodium parasites replicate within red blood cells. During the development within the red blood cell, the parasite digests hemoglobin and crystalizes the otherwise toxic heme. The resulting hemozoin crystals limit imaging by STED nanoscopy owing to their high light-absorbing capacity, which leads to immediate cell destruction upon contact with the laser. Here, we establish CUBIC-P-based clearing of hemozoin crystals, enabling whole-cell STED nanoscopy of parasites within red blood cells. Hemozoin-cleared infected red blood cells could reliably be stained with antibodies, and hence proteins in the hemozoin-containing digestive vacuole membrane, as well as in secretory vesicles of gametocytes, could be imaged at high resolution. Thus, this process is a valuable tool to study and understand parasite biology and the potential molecular mechanisms mediating drug resistance.This article has an associated First Person interview with the first author of the paper.
Gesehen am 31.03.2023